Development of Contextual Teaching Materials Based on the Surrounding Environment in Mathematics for Elementary School Students - Nurjannah, Nurjannah; Syarifuddin; AM, Andi Wahdania; Salmawati; Hikmah, Nur; Haerati; Aliyah, Nurul (Universitas Islam Ahmad dahlan, 2025)
This study aims to develop contextual teaching materials based on the surrounding environment for Grade III Elementary School Mathematics. The development model used is ADDIE, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The needs analysis revealed that both teachers and students require teaching materials relevant to their local environment to enhance mathematical concept understanding. The design phase linked mathematical topics such as arithmetic operations, measurement, and geometry with real-life situations from the students’ surroundings. The developed teaching materials were validated by subject and media experts and tested on Grade III students at SD Negeri 286 Pasaka. Implementation results showed increased student engagement and conceptual understanding. Effectiveness evaluation using n-Gain analysis and student response questionnaires indicated that the developed materials were categorized as